PENGESAMPINGAN KOMPETENSI RELATIF OLEH ASAS HUKUM DALAM SISTEM PERADILAN PERDATA (KAJIAN TERHADAP PUTUSAN NOMOR: 446/Pdt.G/2018/PN.DPS) - Anom, Gusti Ngurah; Andayani Citra, Made Emy (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2021)
To carry out a more flexible market expansion, usually a company will open a branch office. This branch office is a representation of the head office in a certain area. The branch office is an extension of the head office, so that if a dispute arises in business relations and the resolution of the problem reaches the court, the branch office is often positioned as a party to the case, even though according to the provisions in the Law on PT which represents the company in dispute is the head office. The purpose of this paper is to find out whether the lawsuit filed by the plaintiff to the branch office does not violate the court's relative competence, and to determine the relevance of simple, fast and lowcost judicial principles in resolving the case. In this study, this type of research uses normative research by examining Court Decisions, the approach method is by intensively studying material facts (ratio decidendi) in the application of the basis for a lawsuit against the law in Civil Lawsuit No: 466/Pdt.G/2018/PN.DPS. In Denpasar, the results showed that the filing of a lawsuit at the branch office of a company in the form of a Limited Liability Company did not violate the Court's Relative Competence, because the branch office is an extension of the Board of Directors in the head office and carries out duties for the benefit of the head office. The principle of a simple, fast and low-cost trial is very relevant to be applied in this case because the implementation of the case can be more effective and efficient, because the case is handled by the Denpasar District Court so that it can save time, energy and costs.